INTERAKSI PBL-MURDER, MINAT PENJURUSAN, DAN KEMAMPUAN DASAR MATEMATIS TERHADAP PENCAPAIAN KEMAMPUAN BERPIKIR DAN DISPOSISI KRITIS - Maulana, Maulana (Universitas Pendidikan Indonesia, 2015)
Selection of appropriate learning approaches and strategies, will facilitate the achievement of these learning activities. Similarly, in mathematics learning activities in PGSD (department of elementary school preservice teacher), which is demanding the development of a high level of mathematical ability as well as critical thinking skills. However, not many people are trying to look for other factors in addition to the approach/learning strategy, which is possible to contribute to the development of critical thinking skills, such as interest factor majors students (IPA [science] and non-IPA [non-science]) as well as mathematical prior knowledge which has been owned previously. In addition, affective aspects that accompany any critical thinking skills (critical disposition) is a study that is still rare. This paper briefly present to peel the election factor of approaches and learning strategies, ie, problem based learning with